Cardiopulmonary arrest: care after return of spontaneous circulation - dos Santos, Jéssica Batista; Cavalcante, Deives Aurélio Melo da Rocha; Rocha, Claudia Aparecida Godoy; Rodrigues, Fabrícia Tesolin; Diana, Cíntia Cristina Ferreira; da Silva, Rafael Lustosa (Seven Editora, 2023)
Research Question: What are the procedures to be taken during the care of a patient after the return of spontaneous circulation as a result of a Cardiorespiratory arrest? Objective: To identify in the literature what care should be applied in patient care in the face of the return of spontaneous circulation after cardiorespiratory arrest. Hypothesis: Specific care, such as hemodynamic support, correctly performed in the care of patients with post-return of spontaneous circulation, can contribute favorably to their rehabilitation. Type of study: Quantitative method aided by bibliography review methodology. DOI: https://doi.org/10.56238/colleinternhealthscienv1-011